Study on transmission congestion management for restructuring market - Md Amin, Izatti (2014)
The electric power industry has over the years been dominated by large utilities that had overall authority over all activities in generation, transmission and distribution of power within its domain of operation. There were two conditions that are investigated in this research, uncongested and congested condition. The uncongested are condition were there no limitation to buy from any company that more cheap cost than during congested. While, congestion are one or more transmission lines reach their thermal limit and unable to carry additional power, a more expensive generation unit will be scheduled to serve the load. Since the cheaper generators could not reach the load location due to congestion. There were two generic approaches using in this thesis, first uniform market clearing price and locational marginal price (LMP). The uniform market clearing price is define as no transmission bottleneck and losses present during the transportation of the electricity, the cheapest power producer will be selected to serve the loads at all locations and therefore, the electricity price will be the same across the grid. While the LMP is define as the marginal cost of supplying the next increment of electric energy at a specific bus considering the marginal cost and physical aspects of transmission system. In other words, the LMP is the cost to serve one additional MW of load at a specific location, using the lowest production cost of all generators, while observing all transmission constraints. Furthermore, the LMP can be decomposed into three parts: marginal energy price, marginal loss price, and marginal congestion price. The result and analysis has been discussed in this research by comparing between two approaches in different condition. The results obtained are analyzed for further improvements and recommendations.